The 'double-edged effect' of progress in energy-biased technology on energy efficiency: A comparison between the manufacturing sector of China and Japan. (15th September 2020) - Liao, Maolin; Ren, Yufei
Abstract: Based on data of the manufacturing sector of China and Japan from 2003 to 2016, this paper attempts to measure the progresses in energy-biased technology and energy efficiency by constructing a threshold panel regression model with variables including foreign direct investment (FDI) and energy consumption structure to explain energy efficiency using energy-biased technology as the key explaining variable. The estimation indicates significant differences in the energy efficiency of China's and Japan's manufacturing industries. In general, Japan's total energy efficiency is higher than China's. The industry with more intensive technology has higher energy efficiency which rises much faster. The paper finds that the energy efficiency of China's manufacturing sector shows an upward trend in general, while Japan's fluctuates more, showing two peaks and two troughs. Our empirical results show that there is a threshold value of progress in energy-biased technology; below this, progress in energy-biased technology will have a positive effect on energy efficiency and beyond it, the effect will be negative. Since this effect is not one-way, we define it as a 'double-edged effect'. It is estimated that the level of energy-biased technology progress of most manufacturing industries in China is below the threshold value, indicating that the technology progress in China's manufacturing sector has not been excessively biased towards energy consumption, and the impact on energy efficiency is still positive. The China-Japan comparison shows that the threshold value for Japan's manufacturing sector is significantly lower than that for China's, indicating a marginal effect on the 'double-edged effect': The threshold value will decrease when energy efficiency reaches a certain level. Therefore, it is necessary to offset these negative externalities from technological progress with other factors such as by increasing FDI and improving energy consumption structure. Highlights: This paper examines the influence of energy-biased technological progress alone on energy efficiency. It proves the influence of energy-biased technological progress on energy efficiency to be nonlinear. It measures the energy-biased technological progress and energy efficiency of some industries of the manufacturing sector of China and Japan. It proves the rebound effect to be conditional in the manufacturing sector of China and Japan. It also proves the threshold effect in the influence of energy-biased technological progress on energy efficiency.